1995
DOI: 10.1007/bf00341360
|View full text |Cite
|
Sign up to set email alerts
|

Environmental constraints on the growth, photosynthesis and reproductive development of Dryas octopetala at a high Arctic polar semi-desert, Svalbard

Abstract: Opportunities exist in high Arctic polar semidesert communities for colonisation of unvegetated ground by long-lived clonal plants such as Dryas octopetala. This can be achieved by lateral spread of vegetative ramets, or by sexual reproduction and seedling recruitment. The objectives of this study were (1) to determine whether these two means of proliferation show differential sensitivity to contrasting components of the abiotic environment (temperature, soil nutrient and water availability) and (2) to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
137
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(158 citation statements)
references
References 43 publications
16
137
2
1
Order By: Relevance
“…Therefore, N and P levels in Kongsfjorden soils appear low relative to typical microbial nutritional needs. These results are consistent with previous studies on Ny-Alesund soils, which indicated P was more likely limiting than N or K for plant growth (Wookey et al 1995). Measured surface CH 4(g) release rates varied by five orders of magnitude across the sites, ranging from 0.02 to 157.0 lmoles CH 4(g) m -2 h -1 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, N and P levels in Kongsfjorden soils appear low relative to typical microbial nutritional needs. These results are consistent with previous studies on Ny-Alesund soils, which indicated P was more likely limiting than N or K for plant growth (Wookey et al 1995). Measured surface CH 4(g) release rates varied by five orders of magnitude across the sites, ranging from 0.02 to 157.0 lmoles CH 4(g) m -2 h -1 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…In the Arctic, snow depth and rate of snowmelt dictate the duration of time available for resource assimilation by plants (Billings and Bliss, 1959;Galen and Stanton, 1993;Wookey et al, 1994Wookey et al, , 1995Walker et al, 1999), and a short growing season severely constrains vegetative growth (Thó rhallsdó ttir, 1998), in turn influencing reproductive performance of plants. Galen and Stanton (1993) showed a direct link between growing season length and plant performance in alpine buttercups (Ranunculus adoneus) similar to our data for C. tetragona.…”
Section: Discussionmentioning
confidence: 99%
“…Saxifraga oppositifolia and Cassiope tetragona), and there were indications of stronger responses to experimental warming during 'colder' growing seasons (both of which are consistent with Figure 3). Increases in reproductive growth (seed set, seed weight, and germinability) also appear to be general responses to warming in the short-term: Wookey et al (1995), for example, reported a 141% increase in seed germinability of Dryas octopetala at a high arctic polar semidesert, Svalbard, in association with warming over three growing seasons.…”
Section: An Experimental Approach To Understanding Global Warming Andmentioning
confidence: 99%